Assessment of attachment disorder symptoms in foster children: comparing diagnostic assessment tools - Josephine D. Kliewer-Neumann; Janin Zimmermann; Ina Bovenschen; Sandra Gabler; Katrin Lang; Gottfried Spangler; Katja Nowacki (BMC, 2018)
Abstract Background Standardized methods for assessing attachment disorders are scarce but needed for research and practice. Methods In the current study, several assessments for attachment disorder symptoms are used within a German sample of foster children after being exposed to neglect and maltreatment in their biological families. The symptoms were assessed with four established assessment methods based on both parents' report and behavioral observation: The Rating for Infant Stranger Engagement, the Stranger at the Door, the Disturbances of Attachment Interview and the Reactive Attachment Disorder Questionnaire. Results The foster care sample showed symptoms of both the inhibited and the disinhibited attachment disorder. The degree of symptoms is comparable to previous findings. The results of the different tools investigating the disinhibited type of attachment disorder are correlated to each other, but do not overlap. Conclusions Although all approaches are based on the clinical criteria of the DSM-IV, the assessments do not coincide. Each tool provides a different point of view on the symptoms, so a multi methodical approach for assessing attachment disorder symptoms should be implemented. Furthermore, the inhibited and the disinhibited symptoms represent separate categories, as reflected in the DSM-5, requiring separate assessment.